LIVER DISEASE & SICKLE CELL DISEASE: AUTOIMMUNE HEPATITIS MORE THAN A COINCIDENCE; A SYSTEMATIC LITERATURE REVIEW. - Kelvin Lynch; Andrea Mega; Andrea Piccin; Massimo Daves; Helen Fogarty (Mediterranean Journal of Hematology and Infectious Diseases)
• In patients with SCD, chronic liver damage is a common manifestation. More than 50% of SCD patients have elevated liver enzymes. Common underlying aetiologies include sickle cell hepatic crisis, viral hepatitis, sickle cell intrahepatic cholestasis and hepatic sequestration in the acute setting, and cholelithiasis and iron overload in the chronic setting. Autoimmune hepatitis (AIH) is a rare disease that appears to occur more commonly in the sickle cell disease (SCD) population than in the general population. There are many schools of thought as to why this is the case, including the phosphatidylserine hypothesis, the heme inflammatory hypothesis, the complement generation hypothesis, and the transfusion alloimmunization hypothesis.